A survey on injuries among nurses and nursing students: a descriptive epidemiological analysis between 2002 and 2012 in a University Hospital - Stefanati, Armando; Boschetto, Piera; Previato, Sara; Kuhdari, Parvanè; De Paris, Paola; Nardini, Marco; Gabutti, Giovanni (La Medicina del Lavoro, 2015)
Background: Biological risk is the main occupational hazard in hospitals (40-50% of the total). More than 130,000 injuries occur every year in Italy and nurses are the most affected occupational category. Objectives: This study evaluated the incidence of injuries related to biological risk in nurses and nursing students in the University Hospital of Ferrara, how they occur, the knowledge on the topic and on behaviour during the department’s activity. Methods: A retrospective study involving a sample of 8 departments (selected for the occurrence of more than 30 biological injuries between 1st January 2002 and 31 December 2012) recorded injuries related to biological risk; subsequently a cross-sectional survey was carried out through a questionnaire administered to nurses and nursing students. Results: 909 biological accidents were reported (81.18% in nurses and 18.82% in students). Blood was the main biological material involved (83.72% of cases), mostly by percutaneous exposure (84.16%). According to the questionnaire, 53% of subjects reported having had at least one injury during their career, and 5.72% did not report it; 46% reported doing risky procedures (re-capping needles) and 95.45% that they had been informed about the correct use of PPE. Conclusions: The lower percentage of injuries in students could be linked to good university training and to less risky procedures being performed. Re-capping needles remains one of the most dangerous manoeuvers practised. Ongoing training on the correct use of PPE is essential to train prepared and aware health professionals.